The moderating Effect of Social Support on the Relationship between Occupational Stress Interventions and Performance of Academic Staff in A Subset of Public Kenyan Universities - Kinuthia, Jane M.; Kiragu, James (Journal of the Kenya National Commission for UNESCO, 2024)
Occupational stress is a concept that has received a lot of attention from scholars. Knowledge workers, such as academic staff in universities, are prone to suffering from high levels of stress arising from work demands. This study set out to investigate the moderating role of social support in the association between occupational stress interventions and academic staff performance in a subset of Kenyan public universities. The research used a cross-sectional, descriptive, and explanatory design. Three public institutions with a combined total of 3277 academic staff members—Egerton, Kenyatta, and Maseno universities—constituted the observation unit. Using the Krejcie and Morgan formula, the sample size was calculated to be 342. The two-step Zendek and Keppel (2000) method for testing moderation was used in the study. Social support was found to mitigate the connection between academic staff performance and occupational stress interventions at a 95% confidence level. This is a result of social support's ability to reduce stress. Therefore, to have more productive staff members, public institutions should look for ways to assist at the organizational and supervisory levels. To provide the necessary assistance to the workers they supervise, HR managers should also provide social support training to the supervisors. The Job-Demand-Control-Support (JDCS) model supports the moderating influence of social support on the connection between OSI and staff performance.